Public speaking training to sustain teacher professional development in elementary school - Nuzula, Rima Nabilah; Sulaeman, Dedi; Ruminda, Ruminda; Aminuddin, Muhammad (Universitas Islam Malang, 2024)
Teachers in an elementary school located at Arcamanik, Bandung, experienced anxieties when speaking in front of audiences. The study aims to identify teachers' anxieties about public speaking training, evaluate how the training alleviates the anxieties, and assess its impact on teachers' public speaking performance. Qualitative approach is employed in this research by using interviews and observations with ten participants: an English teacher, three classroom teachers, and subject-specific teachers in Indonesian, tahfidz (Qur'anic memorization), Arabic, mathematics, and two Islamic religion teachers. The training was conducted at the beginning of the semester to provide sustained professional development. The findings reveal that there are three categories consisting of new comers, old comers and gender. New comer teachers show a significant growth even more they could eliminate speaking doubts, avoiding negative words, clearer speaking, confidence, more understandable, and engaged in communicating more effectively. Secondly, the old comer teachers tend to be steadier and calmer but have a fast-thinking proficiency in making solutions. Lastly, it seen from gender. Female teachers use public speaking theory the most as compared to male teachers who tend to be more ignorant. All the growth stemmed from the school-facilitated training equipping them for various roles – not only as classroom facilitators but also as service providers interacting with parents and at school event. Researchers recommend holding frequent public speaking workshops to assist teachers in overcoming their speaking anxieties. This can boost confidence and help participants communicate more effectively. Everyone can benefit from practice and tips in a confidential environment.